Historical moral responsibility and manipulation via deletion - De Marco, G (Springer, 2021)
In discussions on moral responsibility for actions, a commonly discussed case is one in which an agent is manipulated into performing some action. On some views, such agents lack responsibility for those actions partly because they issue from attitudes that were acquired in an inappropriate way. In this paper, it is argued that such views are in need of revision. After introducing a new problematic case of a manipulated agent, revisions are offered for specific views. The paper concludes with a discussion of the views in a broader context, as well as some potential implications of the revisions.